A regime analysis of Atlantic winter jet variability applied to evaluate HadGEM3-GC2 - Woollings, T; Masato, G; Williams, P; Hoskins, B; Lee, R (Wiley, 2016)
The behaviour of the eddy-driven jet over the Atlantic sector during the winter season is analysed for the ERA-Interim reanalysis and the coupled and atmosphere-only configuration of HadGEM3-GC2 - the climate model in use at the Met Office. The tri-modal distribution that reveals the jet-stream structure in terms of its preferred locations is reproduced with good accuracy by the model, although a distinct bias towards the high-latitude position is observed. Two different scenarios are found to contribute to this bias. One occurs when the jet shifts from its southern regime, whereby it settles too far north and for too long compared to the reanalysis. The other is associated with the exit from the central latitude regime, with too many events shifting poleward rather than equatorward.Excessively large lower tropospheric eddy heat fluxes during these transitions may account for the jet errors, even though the heat fluxes do not exhibit a climatological bias.Interestingly, these biases are weaker when the atmosphere model is forced with observed SSTs,suggesting that either it is vital to have the correct SST distribution or that ocean-atmosphere coupling plays a key role in the biases. Additional analysis revealed that the Pacific jet exit is biased south in the coupled model and that this is likely to contribute to the Atlantic bias. Anomalously warm SSTs in the Gulf Stream region may be acting together with the Pacific bias in fostering the anomalous activity in the low level eddy heat fluxes.